The Effect of Adding Carboxymethyl Cellulose and Zinc Sulfate on the Corrosion Characteristics of the Drilling Fluid - Al-Rubaiey, Najem A.; Kadhim, Fadhil S. K; Albrazanjy, Mohamed G. Alb (Al-Khwarizmi Engineering Journal, 2019)
Drilling solutions can be considered as an intricate mixture comprising of number of chemical additives which aid specific needs such as controlling the rheological properties and reducing corrosion. Inhibitors are substances that are added in small concentrations to corrosive environment to decrease the corrosion. Their applications can be found in drilling equipments. The effect of adding Zinc Sulphate and Carboxymethyl Cellulose to study their influence on the corrosion of carbon steel in Bentonite mud has been evaluated using Weight Loss Technique. This study focuses on determining rheological properties and corrosion characteristics. Results show CMC and ZnSO4 work as inhibitors when added to the Bentonite with inhibition efficiency was approximately equal to 50%.